Advanced Anode Materials of Potassium Ion Batteries: from Zero Dimension to Three Dimensions - Zheng, Jiefeng; Wu, Yuanji; Sun, Yingjuan; Rong, Jianhua; Li, Hongyan; Niu, Li (Nano-Micro Letters, 2020)
Potassium ion batteries (PIBs) with the prominent advantages of sufficient reserves and economical cost are attractive candidates of new rechargeable batteries for large-grid electrochemical energy storage systems (EESs). However, there are still some obstacles like large size of K+ to commercial PIBs applications. Therefore, rational structural design based on appropriate materials is essential to obtain practical PIBs anode with K+ accommodated and fast diffused. Nanostructural design has been considered as one of the effective strategies to solve these issues owing to unique physicochemical properties. Accordingly, quite a few recent anode materials with different dimensions in PIBs have been reported, mainly involving in carbon materials, metal-based chalcogenides (MCs), metal-based oxides (MOs), and alloying materials. Among these anodes, nanostructural carbon materials with shorter ionic transfer path are beneficial for decreasing the resistances of transportation. Besides, MCs, MOs, and alloying materials with nanostructures can effectively alleviate their stress changes. Herein, these materials are classified into 0D, 1D, 2D, and 3D. Particularly, the relationship between different dimensional structures and the corresponding electrochemical performances has been outlined. Meanwhile, some strategies are proposed to deal with the current disadvantages. Hope that the readers are enlightened from this review to carry out further experiments better. Highlights: 1 This review introduces the recent anode materials of potassium ion batteries classified into 0D, 1D, 2D, and 3D, mainly including carbon materials, metal-based chalcogenides and metal-based oxides, and alloying materials. 2 The advantages, disadvantages, and optimized strategies of different dimensional anode materials are summarized. 3 The relationship between different dimensional anode materials in potassium ion batteries and the corresponding electrochemical performances is outlined. And some strategies are proposed to deal with the current disadvantages of potassium ion batteries.